Synthesis of nanograined zirconium diboride microsphere powder feedstock via emulsification of suspensions. Issue 16 (15th August 2022) - Wat, Amy; Hall, Ashley L.; Yang, Qi Rong (Bruce); Lu, Ryan; Sobalvarro Converse, Elizabeth; Ye, Congwang; King, Gabriella C.S.; Kuntz, Joshua D.; Worsley, Marcus A.; Cahill, James T.; Du Frane, Wyatt L.
Abstract: Ceramic nanograined materials have desirable characteristics compared to their macroparticle counterparts but are rarely used in industrial applications due to issues with poor handleability and health hazards. Due to interparticle forces that become more dominant as the particle size decreases, it is difficult to use nanomaterials to fill dies, spread on surfaces, or flow through hoppers found in various manufacturing processes. Here we report a scalable gelcasting solution and unique emulsification process to create microspheres composed of nanoscale powders to enhance the flowability and handleability of nanomaterials. The gelcasting solution and emulsification process can be used with any nanoparticle composition that can be suspended in a liquid phase. This paper reports the effects of various parameters on zirconium diboride microsphere formation, such as surfactant content and mixing conditions. The microspheres maintain the nano-scale characteristics of the powder but improve its flowability by using cross-linked polyvinyl alcohol to combine irregularly shaped zirconium diboride nanoparticles with a particle diameter of 60 nm into larger spherical particles with a d50 ∼25 μm. This hierarchical feedstock engineering design combine the positive characteristics of materials across both length scales and improve the flowability of the feedstock from a Hausner Ratio of 1.56 to 1.19. The materials produced using this technique can be used in thermal plasma spray, die filling for hot pressing or spark plasma sintering, and binder jet printing applications.